(untitled) (Journal of Comparative & International Higher Education, 2024)
This paper investigates the impact of virtual mentors (VM) on the decision-making process and cultural awareness of prospective international students. It seeks to understand the translative function of virtual mentors by establishing a dialogue between Bourdieu’s cultural intermediation and Barad’s new materialism. Employing a mixed-method approach, the study’s findings indicate that prospective students deem the roles of VM crucial in their international education journey, with technology enhancing their access to resources facilitated by these mentors. However, students express a desire for greater cultural awareness in mentorship interactions within the virtual space. The study recommends that stakeholders should invest in providing culturally responsive digital mentorship to support the experience of both prospective and current international students.